The Therapeutic Effects of West Indian Elm (Guazuma ulmifolia) Leaf Extract on Coronary Artery Atherosclerosis in Hypercholesterolemic Wistar Rats - Ramadhansyah, Reza; Thadeus, Maria Selvester; Muktamiroh, Hikmah; Hardini, Niniek (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to determine the therapeutic effect of West Indian elm leaf extract on coronary artery atherosclerosis in hypercholesterolemia Wistar rats. Cholesterol, a key factor in the pathophysiology of coronary heart disease, is present in fat-containing diets. Orlistat is one of the medications that can reduce blood cholesterol levels, but since it has side effects, herbs are more preferable to it. One such herbal plant, West Indian elm (Guazuma ulmifolia), contains tannins, saponins, alkaloids, and flavonoids, secondary metabolites that carry the properties necessary to reduce blood cholesterol levels, in its leaves. In this experimental study, which focused on histopathological parameters to see the scale of progression of coronary artery atherosclerosis, 30 Wistar rats were induced with a high-fat diet and divided into 6 sample groups, consisting of three control groups (normal, negative, and positive) and three treatment groups (which received a West Indian elm leaf extract at 0.2, 0.4, and 0.8 g/kgBW). Significant results were obtained from both Kruskal-Wallis and Mann-Whitney tests (p<0.05) between the negative control group and the positive control group, between the negative control group and treatment group 2 (0.4 g/kgBW), and between the negative control group and treatment group 3 (0.8 g/kgBW). In conclusion, this study proved that West Indian elm (Guazuma ulmifolia) leaf extract reduces the development of coronary atherosclerosis and shares a similarity in therapeutic effect with orlistat.